Ultrasound Microbubble-Mediated microRNA-505 Regulates Cervical Cancer Cell Growth via AKT2 - Leilei Xu; Qin Zhang; Changhua Li; Fu Hua; Xiaoping Liu (Analytical Cellular Pathology)
The application of ultrasound and microbubbles (USMB-) mediated microRNA (miR) is a promising approach of gene delivery for cancer treatment. We aimed to discuss the effects of USMB-miR-505 on cervical cancer (CC) development. miR-505 mediated by USMB was prepared. The effect of miR-505 on its transfection efficiency and the effect of miR-505 on HeLa cell proliferation, cell cycle, apoptosis, migration, and invasion were studied. The target gene of miR-505 was predicted, and its expression in CC was detected. The effect of the target gene on HeLa cells was further verified. USMB-miR-505 showed a higher transfection efficiency than miR-505 alone. The inhibitory effect of miR-505 mediated by USMB on HeLa cells was better than miR-505. miR-505 targeted AKT2, which was upregulated in CC. Overexpression of AKT2 reversed the inhibitory effect of USMB-miR-505 on HeLa cell malignant behaviors. Overall, we highlighted that USMB-miR-505 inhibited HeLa cell malignant behaviors by targeting AKT2.